Characterization of F-region neutral wind response times and its controlling factors during substorms - Davidson, Katherine; Zou, Ying; Lamarche, Leslie; Bhatt, Asti; Conde, Mark (Frontiers in Astronomy and Space Sciences, 2025)
Ion-neutral coupling is responsible for dissipating energy deposited into the high-latitude ionosphere during geomagnetically active periods. The neutral wind response time, or the ion-neutral coupling efficiency, is not well characterized, with a wide range of reported response times. Additionally, how this coupling efficiency varies with geomagnetic activity level is not well understood, with few studies addressing the impact of geomagnetic activity level on neutral wind response time. In this study, a statistical analysis of the neutral wind response time during substorm periods is performed. We use data from Scanning Doppler Imagers (SDIs) and the Poker Flat Incoherent Scatter Radar (PFISR) to calculate the neutral wind response time using the new weighted windowed time-lagged correlation method. Substorm events were found using SuperMAG substorm lists and All Sky Imagers (ASIs). This statistical analysis resulted in 23 substorm events, with an average response time of ∼16 min. To determine the controlling factors of this response time, geomagnetic and ionospheric parameters, such as IMF strength and orientation, SYM/H index, AE index, and electron density, are investigated for the statistical substorm set. A superposed epoch analysis of the parameters is performed to determine average geospace conditions required for fast neutral wind responses. It was found that quiet-time conditions in AE and SYM-H indices, a southward turning of IMF around 1.5 h before substorm onset time, and large electron densities lead to faster neutral wind response times. Based on the geomagnetic indices results, it was suggested that thermospheric pre-conditioning may play a role in neutral wind response times.